Agreement on Ownership of the Mount Carmel Modern Cemetery Land Plot Between PT Pagoda Karya Abadi and the Semarang Regency Government: Perjanjian Tentang Kepemilikan Kavling Tanah Makam Modern Mount Carmel Antara PT Pagoda Karya Abadi dengan Pemerintah Daerah Kabupaten Semarang - Freddy Wahyu K.S. (Universitas Negeri Semarang, 2012)
Modern cemetery is one of the needs of people who have not been so arranged and cared for by the government. The existence of Mount Carmel to cause problems with the local government district of Semarang. After a change of leadership through the General Election in 2010, permitting offense by Mount Carmel Semarang Regency through the Commission D which is also a product of the 2009 election. This study aims to analyze the cemetery land deal from the perspective of contract law. The approach used is the juridical-normative approach. These results indicate that the problem raised Semarang Regency is the management of Mount Carmel ”judged” is not permitted. Semarang Regency also argued that according to the PP and Permendagri, cemetery land ownership is limited to the right to use and has provisions limit boundary area. The rest are not justified cemetery controlled by individuals, as well as commercial and should not be exclusive. Eventually these problems culminated with the recommendation of Parliament to the executive order to close the temporary management of Mount Carmel in March 2011 to the Pagoda PT Karya Abadi complete the requirements given by the Parliament.